Preparation of Metal-Organic Framework Materials and Their Adsorption Performance for Methylene Blue in Wastewater Treatment - Crouse, Tshiamo; Langmi, Nichola; Saghi, Majid (Journal of Green Energy and Environmental Engineering, 2025)
The rapid development of industry in China has improved economic levels but also led to severe environmental pollution. Water contamination ranks among the planet’s three most critical environmental crises and has remained a persistent priority for scientists, regulators, and the public alike. Colored organic dyes discharged from industries such as textiles and printing are toxic and difficult to degrade, posing risks to human health and causing serious damage to the ecosystem. This work systematically synthesizes the MIL-68(In) family and maps how pendant functional groups perturb the framework, quantifying changes in BET area, micropore volume, and overall crystallinity. The adsorption performance of both unmodified and modified MIL-68(In) materials for methylene blue (MB) in industrial wastewater was examined. Core work was carried out in four stages. (1) Crystalline MIL-68(In) and its amino derivative were prepared under solvothermal conditions. (2) The products were analysed by powder XRD, nitrogen physisorption, SEM/TEM imaging and FT-IR to establish phase purity, porosity, particle shape and surface chemistry; the effect of reaction temperature, time and precursor ratio on framework formation was also mapped. (3) Three sorbents—pristine MOF, NH₂-tagged MOF and thiol–carboxyl-enriched MOF (MIL-68(In)-SC)—were screened for the removal of the cationic dye methylene blue. (4) Equilibrium tests revealed that the engineered thiol–carboxyl variant outperformed the parent solids, giving 96.6 % uptake within 2 h and a Langmuir capacity of 204 mg g⁻¹, roughly double that of the unmodified material. The findings demonstrate that MIL-68(In)-SC has practical application value for adsorbing MB from wastewater.